Integrasi Pola Kerjasama Komite Madrasah dan Kepala Madrasah dalam Pengembangan Pendidikan Islam - Asnawan Asnawan (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2019)
This paper is about the pattern of cooperation between the committee and the head of the madrasa in the form of a monthly meeting. On the agenda of the monthly meeting usually discuss what are the problems that exist, or reporting about the financial that has been obtained and issued. In cooperation between the committee and the head of the madrasah, individuals are established in a good relationship, with the concept of mutual respect and mutual respect. Relationships that, like if a problem occurs, can be solved by giving suggestions or considerations in solving existing problems or with communication links, holding meetings for deliberations to reach consensus. In addition, relationships are woven by providing motivation and support in development. The relationship is horizontal means that the line has a specific goal including coordinating tasks, sharing information for planning and activities, solving problems that arise between people who are in the same level, guaranteeing the same understanding.